Optimization of Filter and Operational Amplifier Based on Evolutionary Strategy. Issue 1 (January 2021) - Lu, Tengteng; Luo, Chao; Xu, Jun; Guo, Guoping
Abstract: Optimization of analog circuits relies on engineers' experience and intuition to find suitable parameters to satisfy circuit specifications. This job is highly labor-intensive, highly repetitive, and time-consuming, but the optimized circuit is sub-optimal. In this paper, the evolutionary strategy is proposed to optimize analog circuit design strategy. The filter designed by engineers and operational amplifier with random generated instances' parameters are included, and the S parameters of the filter and the gain and dynamic power consumption of the operational amplifier are optimized respectively. The simulation results show that the filter and operational amplifier can be further optimized by using the evolutionary strategy. This method can greatly reduce the workload of analog circuit designers, improve the performance of analog circuits and shorten the design cycle.